2023
DOI: 10.18814/epiiugs/2022/022009
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal subsidence over Pabdana coal mine Kerman Province, central Iran using time-series of Sentinel-1 remote sensing imagery

Abstract: Environmental monitoring of mining regions using satellite imagery is crucial for sustainable exploitation and preventing geohazards. Movements due to the failure of the roof in underground coal mining, by migrating upwards and outwards from the seam being mined, could eventually appear as ground deformation. To investigate the matter further, the surface deformation that occurred over the Pabdana mining area was monitored in three time periods, between October 2, 2014, and July 27, 2019. Persistent scatterer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…As a result, the subsidence on the point increases continuously and gradually approaches the maximum magnitude; the subsidence process may last for several years or decades. Basically, the subsidence curve at a ground point with respect to time is very close to an inverse S-shaped curve, as revealed in many previous studies [25,26]. It can be seen from Figure 10 that the GNSS-observed and the model-predicted subsidence curves have good accordance with these previous studies for all four stations; i.e., the time series of the subsidence presents as an inverse S-shaped curve in general.…”
Section: Dynamic Ground Subsidencesupporting
confidence: 84%
See 1 more Smart Citation
“…As a result, the subsidence on the point increases continuously and gradually approaches the maximum magnitude; the subsidence process may last for several years or decades. Basically, the subsidence curve at a ground point with respect to time is very close to an inverse S-shaped curve, as revealed in many previous studies [25,26]. It can be seen from Figure 10 that the GNSS-observed and the model-predicted subsidence curves have good accordance with these previous studies for all four stations; i.e., the time series of the subsidence presents as an inverse S-shaped curve in general.…”
Section: Dynamic Ground Subsidencesupporting
confidence: 84%
“…As studied in [25][26][27], the variation pattern of subsidence induced by underground coal mining at a given ground point is very similar to a reverse "S" curve. This typical variation pattern of subsidence cannot be described by the Knothe model, as evidenced in Figure 3, which shows an example of a subsidence time series calculated using three typical models when the maximum ground subsidence is 4000 mm.…”
Section: Typical Dynamic Prediction Models For Ground Subsidencementioning
confidence: 85%
“…Dychkovskiy et al [43] investigated the stresses existing during dynamic processes in the rock mass. The modern directions of numerical modeling of rock masses during underground mining were also widely discussed in the literature [44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…The organic phase is composed of fixed carbon and volatiles while the inorganic phase contains sulfides, carbonates, and clay minerals (Cheng et al, 2014;Zhou et al, 2014;Sahoo et al, 2017). Majority of the critical elements and minerals are associated with organic matter, while a rare amount of minerals occurred during the inorganic phase (Li et al, 2011;Mehrabi et al, 2022). It has been found that sulfide minerals such as pyrite and marcasite are abundantly present in coals, which generally cause corrosion of boiler tubes, heat resistance, and cause pollution by the emission of sulfur dioxide during combustion (Dai et al, 2012;Zhou et al, 2014;Xia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%